The effect of nozzle inclination on heat transfer in jet impingement systems - Oladiran, M. T. (Cranfield University, 1981)
Jet impingement heating and cooling techniques are used extensively in industrial applications. in some of these installations, the axis of the jet can be inclined relative to the impingement surface. The impingement flow is then unsynLmetrical so that the heat transfer rates are modified. At present, there is a lack of information concerning the effect of inclination on jet impingement heat transfer. Thus, the experimental study reported in this thesis is primarily concerned with the measurement of local and average heat transfer coefficients associated with the impingement of inclined turbulent circular jets onto flat plates. A single free jet exiting into initially stagnant surroundings was considered and the nozzle inclination was varied from 300 to 900 to the surface. The tests covered the range: Z/d (nozzle-target separation) of 6 to 16 and Re (jet Reynolds number based on exit conditions) of 32500 to 65000. The effect of the exit nozzle shape was also determined. In multiple jet systems, the flow from the upstream jets can significantly affect those situated in the downstream section. Thus, the effect of nozzle inclination on the performance of an impinging jet exiting into a cross flow was also investigated. Thus, as well as the angle of inclination (a), the magnitude of the cross flow (Uc) and the width of the duct (H/d) were also altered in this confined situation. The ranges of these variables were 300<a<l350,55Uj/Uc520.9 and UH/d426. A 'thin--film' naphthalene sublimation technique was used to measure the variation of the mass transfer rates over the impingement surface and these rates were converted to heat transfer data by invoking the Chilton-Colburn analogy between the two processes. The average heat transfer coefficients quoted in the'text were obtained by numerically integrating the local values. The thin-film naphthalene sublimation technique yielded repeatable results which were generally in good agreement with published data for the limited cases for which comparisons-were possible. ' For the unconfined jets, inclining the nozzle reduced the heat transfer rates. The stagnation point, impingement region and average heat transfer coefficients were correlated by means of simple power law relationships which involved the Reynolds number (Re), the nozzle-target separation (z/d) and the angle of inclination (a). Both circular and elliptical-shaped nozzles produced essentially similar results so that it appears that the shape of the velocity profile at the jet exit can be neglected for the conditions studied in this invest: i. gation. For the confined situations, it was found that superimposing a cross flow onto the jet reduced the heat transfer rates and this is in agreement with the results of previous investigators. At low cross flows, inclining the nozzle further reduced the heat transfer rates. However, at higher cross flows, inclining the nozzle could lead to an increase in heat transfer rates and an angle of inclination of approximately 600 was found to yield optimal results. This optimal appears to result from a balance between two conflicting effects, namely that inclination reduces heat transfer but also simultaneously increases the penetration of the jet upstream into the cross flow. Limited velocity and turbulence measurements were undertaken for the jets in order to characterise the flow. These measurements were in good agreement with data from previous investigations so that the heat transfer results from this study should be applicable in a fairly general manner. In order to explain the heat transfer results, flow visualization studies were also carried out.